Changes in the Influence of Alcohol-Paired Stimuli on Alcohol Seeking across Extended Training - Corbit, Laura H.; Janak, Patricia H. (Frontiers in Psychiatry, 2016)
Previous work has demonstrated that goal-directed control of alcohol seeking and other drug-related behaviors is reduced following extended self-administration and drug exposure. Here we examined how the magnitude of stimulus influences on responding changes across similar training and drug exposure. Rats self-administered alcohol or sucrose for two or eight weeks. Previous work has shown that eight, but not two weeks of self-administration produces habitual alcohol seeking. Next, all animals received equivalent Pavlovian conditioning sessions where a discrete stimulus predicted the delivery of alcohol or sucrose. Finally, the impact of the stimuli on ongoing instrumental responding was examined in a Pavlovian-instrumental transfer (PIT) test. While a significant PIT effect was observed following two weeks of either alcohol or sucrose self-administration, the magnitude of this effect was greater following eight weeks of training. The specificity of the PIT effect appeared unchanged by extended training. While it is well established that evaluation of the outcome of responding contributes less to behavioral control following extended training and/or drug exposure, our data indicate that reward-predictive stimuli have a stronger contribution to responding after extended training. Together, these findings provide insight into the factors that control behavior after extended drug use which will be important for developing effective methods for controlling and ideally reducing these behaviors.